Legal Institutions Facilitating Institutions as Determinants of Banking Operational Policy Direction - Arya Salwa Wardana; Gunardi Lie; Moody Rizqy Syailendra Putra (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This study aims to examine the role of bank facilitating institutions and their functions in relation to the policy of banking business activities in Indonesia in carrying out the management system and work system of the bank. In this study the authors used explanatory qualitative research methods, data were obtained from official sources related to information regarding the roles and functions of facilitating institutions with Islamic banking financial institutions as well as from book reference sources and other relevant references. The author finds that overall the bank facilitator institution plays an important role as an institution that supports the running of Islamic bank activities in a proportional and orderly manner. And the authors found that according to LPS information, so far there have been no Islamic banks, especially those that have failed banks or banks whose existence needs to be saved. The essence of the role and function of the facilitating institution is very closely related to financial institutions. And each institution has different authorities, functions and duties in supervising, overseeing, protecting, resolving problems, issuing fatwas related to bank products and regulations regarding work systems. The main function of the bank facilitating institution is to support bank business activities so that they run effectively and in a sound and orderly manner.